Historical process and public policies related to palliative care in Brazil - Sousa, Luísa Pedrada de; Souto, Laísa de Souza; Barbosa, Roberta Ribeiro Batista (Seven Editora, 2024)
Palliative Care is a concept focused on improving the quality of life for patients and families in the face of life-threatening illnesses. Its principles include symptom relief, affirmation of life, consideration of death as a natural part, integration of psychological and spiritual aspects, active support to the patient until death, support to family members, and a multidisciplinary approach. In Brazil, the implementation of this concept must be aligned with national health policies, based on constitutional principles such as universality and equality. Resolution No. 41/2018, approved by the Tripartite Interagency Commission of the Ministry of Health, establishes guidelines for the organization of palliative care in the Unified Health System (SUS), considering the demographic transition and epidemiological changes. Although the SUS already superficially addresses palliative care, it still does not treat it as a public health policy with clear guidelines. The reorganization of the care model implies reviewing spaces, management, technologies, training of professionals and communication models, shifting the focus from recovery to the care and comfort of the patient. The need to integrate palliative care at all levels of health care in the SUS is highlighted, making its implementation a priority in the face of the growing technoization of medicine, which often neglects the autonomy and dignity of the patient. The implementation of these guidelines will contribute to a more humanized and comprehensive approach to the SUS care network, recognizing palliative care as an essential component of health care. DOI:https://doi.org/10.56238/sevened2024.001-044